Tractor performance in function of storage period and different proportions of biodiesel and diesel - de Oliveira, Melina Cais Jejcic [UNESP]; Lopes, Afonso [UNESP]; de Lima, Leomar Paulo; Neves, Murilo Coelho Theodoro [UNESP]; Yamaguti, Priscila Sawasaki [UNESP]; Lira, Thyago Augusto Medeiros [UNESP]; Moreti, Thaisa Calvo Fugineri [UNESP]; Koike, Gilberto Hirotsugu Azevedo (My University, 2015)
Biodiesel is a renewable and biodegradable fuel produced from vegetable oil or animal fat by transesterification. The viability of this product as an alternative source of energy depends on several factors such as blend proportion and stability during storage since the availability of raw materials is seasonal and varies according to the harvest of each crop. This study aimed to evaluate the operational performance and the smoke density of the tractor operating on biodiesel from castor oil. The factors studied were the storage period and biodiesel/diesel blend proportion. The fuel storage periods was zero, three and six months after the date of production and biodiesel/diesel blend proportions were 0% of biodiesel (B0), 5% of biodiesel (B5), 25% of biodiesel (B25), 50% of biodiesel (B50) and 100% of biodiesel (B100). The results showed an increase in the specific fuel consumption from the blend with 25% biodiesel, however, the storage period had no effect on consumption. Smoke density was reduced with the addition of 5% biodiesel, noting that the storage period influenced this variable.
Keywords: Bioenergy; Biofuel; Farm tractors test; Ricinus communis L; Smoke density; Specific fuel consumption